Expert systems principles and programming (photo) - C. Giarratano Joseph (Course Technology, 2005)
This book combines coverage of expert systems theory with coverage of practical applications using CLIPS, an expert systems shell widely used in government, industry, and education. The first part of the book (Chapters 1-6) presents the underlying theory behind expert systems and how they fit into the scope of computer science; that is the logic, probability, data structures, AI, and other topics that form the theory of expert systems. Learning the advantages and disadvantages of expert systems, students will be able to make informed decisions regarding the appropriate use of expert system technology. The second half (Chapters 7-12) is an introduction to the CLIPS expert system tool which now also includes coverage of the procedural and object-oriented capabilities. This part is a practical introduction to expert system programming that serves to reinforce and clarify the theoretical concepts developed in the first part.